Addressing Market-Access Concerns of Developing Countries arising from Environmental and Health Requirements Lessons from National Experiences - Andrew, Dale (OECD Publishing, 2004)
This report represents the stock-taking of the lessons learned from a series of twenty OECD case studies which examined specific market access problems arising from environmental and health requirements faced by developing country exporters. Together with a series of UNCTAD case studies and the experiences exchanged at an OECD Global Forum on Trade workshop, held in New Delhi in November 2002, the focus is on the approaches that contributed to addressing the market access difficulties. These are divided into two sections: first, those addressing information flows and capacity building needs of developing-country exporters, undertaken both by governments and non-governmental organisations; and then the procedures in developing, implementing and reviewing regulations and standards. While covering a range of natural resource-based exports and manufactures and one traded service in key OECD import markets, no generalisation can be drawn regarding the scale of the market-access problems created by environmental and health requirements
Keywords: Trade